2017
DOI: 10.15252/emmm.201607315
|View full text |Cite
|
Sign up to set email alerts
|

MG132‐induced progerin clearance is mediated by autophagy activation and splicing regulation

Abstract: Hutchinson–Gilford progeria syndrome (HGPS) is a lethal premature and accelerated aging disease caused by a de novo point mutation in LMNA encoding A‐type lamins. Progerin, a truncated and toxic prelamin A issued from aberrant splicing, accumulates in HGPS cells' nuclei and is a hallmark of the disease. Small amounts of progerin are also produced during normal aging. We show that progerin is sequestered into abnormally shaped promyelocytic nuclear bodies, identified as novel biomarkers in late passage HGPS cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 85 publications
11
85
2
Order By: Relevance
“…Autophagy activation has been viewed as a compensatory protein degradation mechanism when proteasome function is inhibited [18, 39]. In agreement to this, our results also demonstrated that MG132 treatment significantly increased LC3II conversion along with accumulation of poly-ubiquitinated proteins in HEK293 cells transiently transfected with either vector control or myc-tagged EBNA3C (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Autophagy activation has been viewed as a compensatory protein degradation mechanism when proteasome function is inhibited [18, 39]. In agreement to this, our results also demonstrated that MG132 treatment significantly increased LC3II conversion along with accumulation of poly-ubiquitinated proteins in HEK293 cells transiently transfected with either vector control or myc-tagged EBNA3C (Fig.…”
Section: Resultssupporting
confidence: 89%
“…MG132 treatment was shown to enhance progerin clearance through autophagy and regulating splicing mechanisms by downregulating SRSF-1 [39]. Besides its proteolytic functions, proteasomal machinery also provides non-proteolytic activities engaging transcriptional and post-transcriptional regulation of multiple cellular genes [39,66,84]. In agreement to this, our RNA-seq data reveals that proteasomal inhibition enhances transcriptional activation of genes (viz.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Lamins are type V intermediate filament proteins that form the nuclear lamina, a filamentous network underlying the inner nuclear membrane of eukaryotic cells . Mutation, aberrant splicing and abnormal expression of lamin A/C, the nuclear A‐type lamins, will lead to the disruption of various crucial cellular functions and result in a number of devastating diseases. For example, in the cardiovascular system, mutation of lamin A/C caused by Lmna mutations participates in up to 10% of dilated cardiomyopathies (DCMs) and underlies a spectrum of other diseases including muscular dystrophy, lipodystrophy and acrogeria syndromes .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear defects in HGPS cells can be largely alleviated by farnesyltransferase inhibitors (FTIs) (Capell et al, 2005; Hamczyk et al, 2018; Toth et al, 2005). However, disruption to other nuclear compartments, such as nuclear bodies, in HGPS is rarely reported (Harhouri et al, 2017). A recent study identified disordered structures of PML NB in late passage of cultured HGPS cells (Harhouri et al, 2017); this study, however, did not clarify their function or effects on cellular processes.…”
Section: Introductionmentioning
confidence: 99%